Sistem Pakar Diagnosa Penyakit Akibat Virus Pada Manusia Menggunakan Metode Teorema Bayes - Hadi, Wahyu Nofiyan; Suhartini, Titik (Universitas Nahdlatul Ulama Blitar, 2024)
An expert system is a computerized application that aims to imitate the reasoning process of an expert in solving certain problems and making decisions or conclusions because their knowledge is stored in a knowledge base to process problem solving. The basis of an expert system is how an expert's knowledge is transferred to a computer and used to make decisions and draw conclusions based on that knowledge. Many expert system applications have emerged in the medical field. By answering questions on an application similar to consulting a doctor, this expert system allows ordinary people to detect diseases based on the symptoms they experience. In this way, lay people can also identify diseases and treatment solutions early, which allows for rapid treatment and disease prevention. This system aims to provide support to medical personnel in carrying out initial diagnoses, increasing diagnostic accuracy, and assisting in making medical decisions more quickly and efficiently. The use of the Bayes Theorem method allows the system to handle uncertainty and variations in the symptoms experienced by patients, so as to provide more accurate results.